MicroRNA-7, synergizes with RORα, negatively controls the pathology of brain tissue inflammation - Yue, Dongxu (J Neuroinflammation, 2020)
BACKGROUND: Accumulating evidence has documented that microRNA-7 (miR-7) plays an important role in the pathology of various diseases. However, the potential role of miR-7 in brain tissue inflammation (BTI) remains unclear. METHODS: We detected the expression of miR-7 in LPS-induced murine BTI model and observed the possible effects of miR-7 deficiency on the pathology of BTI. To elucidate the mechanism, the target gene of miR-7 was screened out by Gene chip assay and its potential roles in BTI were evaluated by Western blot, immunofluorescence, and RNAi assay, respectively. RESULTS: MiR-7 was upregulated in brain tissue in BTI mice and its deficiency could significantly aggravate the pathology of brain tissue. Moreover, RORα, a new target molecule of miR-7, was upregulated in brain tissue from miR-7 deficiency BTI mice. Of note, downregulation of RORα could remarkably exacerbate the pathology of brain tissue and elevate the transduction of NF-κB and ERK1/2 signaling pathways in brain tissue from miR-7 deficiency BTI mice. Furthermore, RORα and miR-7 were dominantly co-expressed in neurons of BTI mice. Finally, RORα synergized with miR-7 to control the inflammatory reaction of neuronal cells in response to LPS stimulation. CONCLUSIONS: MiR-7 expression is upregulated in BTI model. Moreover, miR-7 synergizes with its target gene RORα to control the inflammation reaction of neurons, thereby orchestrating the pathology of BTI.